PENGEMBANGAN MEDIA VIDEO ANIMASI CANVA UNTUK MENINGKATKAN LITERASI SAINS SISWA SEKOLAH DASAR DI KABUPATEN SIDOARJO - Ulimawati, Yetti; Roesminingsih, Erny; Rumanta, Maman (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
This research aims to look at students' development in new media and the contribution of science learning innovations based on creative video animation using Canva to increase scientific literacy in elementary schools on energy sources and changes to increase students' scientific literacy in cluster 01 of Sidoarjo sub-district. This research method is research and development (RD) with the development model in this research referring to the RD model design of Borg Gall (1988). Purposive sampling in this study was group 01, namely grade 3 students at SDN Pucang 1, SDN Pucang 2, SDN Pucang 3, SDN Pucang 4, SDN Sidoklumpuk, SDN Sidokumpul.  Research conducted using canvas animation video media in 6 schools or clusters of 01 grade 3 elementary school students in Sidoarjo proved that it significantly increased students' scientific literacy by 16.5%. It is hoped that researchers can make more complex observations by comparing gender, and not just limited to grade 3 elementary school students, they can compare the learning process in grades 4, 5, 6 and use other variables such as level of self-confidence and others.